2007
DOI: 10.1557/jmr.2007.0319
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of anatase N–F-codoped TiO2 sol and its photocatalytic degradation for formaldehyde

Abstract: Anatase nitrogen and fluoride codoped TiO2 sol (N–F–TiO2) catalysts were fabricated by a modified sol-gel hydrothermal method, using tetrabutyl titanate as precursor. The microstructure and morphology of sol sample were characterized by x-ray diffraction (XRD), transmission electron microscopy (TEM), ultraviolet-visible dielectric relaxation spectroscopy (UV-VIS-DRS), x-ray photoelectron spectroscopy (XPS), etc. It was shown that N–F–TiO2 particles in sol were partly crystallized to anatase structure and dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Enormous efforts have been made to enhance the photocatalytic performance of TiO 2 . 10 For example, the strategies involving the metal or metal oxide deposition, [11][12][13] nonmetal element doping, [14][15][16][17] coupling of composite semiconductors, 18 and surface sensitization, 19 etc. have been confirmed to be effective for the promotion of the photocatalytic activity of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Enormous efforts have been made to enhance the photocatalytic performance of TiO 2 . 10 For example, the strategies involving the metal or metal oxide deposition, [11][12][13] nonmetal element doping, [14][15][16][17] coupling of composite semiconductors, 18 and surface sensitization, 19 etc. have been confirmed to be effective for the promotion of the photocatalytic activity of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalytic degradation of HCHO is conducted using a variety of catalysts, including SiO 2 , [ 6 ] TiO 2 , [ 6,7 ] SnO 2 , [ 1 ] ZnO, [ 5 ] and Bi 2 O 3 . [ 8 ] Recently, TiO 2 has become a promising photocatalyst for HCHO decomposition due to its strong oxidation power, outstanding optical and electrical properties, biological and chemical inertness, nontoxicity, and cost‐effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the HCHO elimination has received considerable research interest due to its harm to human health and environment. [ 1–9 ] For instance, Li et al [ 2 ] have prepared the CeGOTiO 2 ternary composites using sol–gel method and demonstrated that the presence of Ce (0.4 wt%) and GO (0.2 wt%) led to the HCHO degradation of 83.8% under simulated sunlight for 7 h. However, the utilization of TiO 2 /rGO nanocomposite is mainly focused on water splitting, [ 11 ] degradation of dyes, such as rhodamine B [ 17 ] and methylene blue, [ 18 ] and treatment of organic solvents, such as formic acid and acetone. [ 14,15 ] In 2013, Huang et al [ 9 ] have synthesized TiO 2 /GR composites by the solvothermal method and utilized tetra‐butyl orthotitanate (TBOT) as a Ti source and expensive GR as a C source.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, F. Huang adopted a facile hydrothermal method to synthesize hierarchical TiO 2 and Nb 3 O 7 F nanomaterials when he investigated the chemical properties of boride ceramic. 9,10 It further needs to confirm whether this method could be applied to the preparation of ZrO 2 nanomaterials or not.…”
Section: Introductionmentioning
confidence: 99%